Solution for smart government cloud based on cloud security technology - Qianhua ZHANG; Jianwu ZHANG (Dianxin kexue)
The national Twelfth Five-year Plan have proposed to strengthen information sharing and austerity,government cloud development are planning this plan. Governments across the country are integrating hardware and software resources to jointly build a public e-government platform.With the promotion of government cloud,the implementation of the problem will follow. Government cloud construction needs to solve the problem of information islands among government departments,while taking into account the security risks of cloud computing technology.From the point of view of security inheritance, e-government cloud business is still a government business system, which need a high degree of security protection.From the point of view of security compliance,the government bureau of the commission need to be classified according to its importance. Combined with the current cloud security technology, a kind of e-government cloud solution was put forward, which provided a comprehensive security scheme for security system planning,security automation deployment and security supervision.